Calcium Phosphate Nanoparticles Tested on Hydroxyapatite Discs as Remineralising Agent. (2022) - Mok, Z.H.; Mylonas, P.; Austin, R.; Proctor, G.; Pitts, N.; Thanou, M.
Abstract : Purpose/Aim: To investigate the remineralisation properties of novel calcium phosphate nanoparticles (CPNPs) on hydroxyapatite (HA) discs as an alternative substrate model to enamel at different pH levels. Materials and Methods: Colloidally stable CPNPs (2% w/v) were prepared via co-precipitation of calcium chloride and sodium phosphate, and sodium citrate (100 mM) added post-precipitation as the capping agent. Particle size and morphology were characterised with dynamic light scattering and scanning electron microscopy (SEM). Crystallinity was assessed with Fourier-transform infrared spectroscopy, Raman spectroscopy and X-ray diffraction, and the Ca/P ratio with inductively coupled plasma mass spectroscopy and total reflection X-ray fluorescence spectroscopy. HA discs were eroded in acetate buffer (0.5 M; pH 4.0) at various timepoints (1, 5, 10, 30 min, and 2, 4 h) to produce a suitably eroded substrate for remineralisation. Their physical differences compared to enamel, together with remineralisation outcome at different pH levels were assessed by Knoop microhardness, surface roughness and step height by a profilometer, SEM and light microscope. Results: Colloidally stable CPNPs of 60 nm, zeta potential -23.3 1.3 mV, with high HA crystallinity and a Ca/P ratio of 1.54 had been produced. HA discs eroded for 2 h showed a 2 m step height and were deemed suitable to be used as a demineralised artificial substrate model for remineralisation. It was established that CPNPs were heterogeneously deposited on the HA discs at pH 9.2, whereas newly precipitated minerals from CPNPs were potentially formed at pH 6.2. Conclusions: Citrate-stabilised CPNPs with high HA crystallinity showed detectable surface remineralisation properties on HA discs.